Software Process Assessment in Scrum with a Kanban-Based Organization - Pėkis, Vaidotas; Peldžius, Stasys (Information & Media, 2018)
Seeking for a higher quality of developing products, organizations often look for ways to improve their software development process. Consequently, the probability of winning a contest increases, since projects can be finished faster together with sticking to budget and meeting deadlines. Various models of process assessment can be used to evaluate the development process of a company. Organizations tend to choose them using one or another software development methodology or framework in order to improve the assessment. But in the long-term period, the methodology chosen first often appears to be insufficient in achieving a higher maturity of the process; therefore, this leads to the implementation of additional methodologies. It is critical for the organization to know how a chosen methodology will affect its maturity. This paper investigates how the CMMI-DEV assessment of the development process changes when the organization, using Scrum as the base of its software development process, extends it with Kanban. It was found that an organization combining Scrum together with Kanban would increase the number of fully implemented practices by 75%.
Keywords: software development methodology; Scrum; Kanban; CMMI-DEV; maturity level of organization